Sociodemographic and clinical characteristics associated with vitamin D status in newly diagnosed pediatric cancer patients. (18th May 2020) - Aristizabal, Paula; Sherer, Michael; Perdomo, Bianca P.; Castelao, Esteban; Thornburg, Courtney D.; Proudfoot, James; Jacobs, Elizabeth; Newfield, Ron S.; Zage, Peter; Roberts, William; Martinez, Maria Elena
Abstract: Vitamin D deficiency and insufficiency are associated with serious sequelae in childhood cancer survivors. However, data on vitamin D deficiency in children with newly diagnosed cancer are scarce and the role of sociodemographic factors and vitamin D supplementation is largely unknown. We assessed vitamin D status and its socio-demographic and clinical correlates in 163 children with newly diagnosed cancer, using 25-hydroxy vitamin D (25(OH)D) concentrations and assessed longitudinal changes following vitamin D supplementation. Sixty-five percent of the patients with newly diagnosed cancer had low 25(OH)D concentrations. Fifty-two patients (32%) were vitamin D deficient (≤20 ng/mL 25(OH)D concentration), and 53(33%) were insufficient (21-29 ng/mL 25(OH)D concentration). Age over 10 ( P  = 0.019), Hispanic ethnicity ( P  = 0.002), and female sex ( P  = 0.008) were significantly associated with lower 25(OH)D concentration at diagnosis. Vitamin D supplementation resulted in significant increase in 25(OH)D concentrations ( P  < 0.001). However, following supplementation in the longitudinal analysis, this increase was less pronounced in Hispanic patients vs. non-Hispanic ( P  = 0.007), and in children with solid tumors vs. hematological malignancies ( P  = 0.003). Vitamin D deficiency and insufficiency are common in children with newly diagnosed cancer. Hispanic patients, females and older children were at higher risk for vitamin D deficiency and insufficiency. Although supplementation appeared to increase 25(OH)D concentrations over time, this increase was not as pronounced in certain subsets of patients. Prospective trials of the effects of vitamin D supplementation on bone health in children with newly diagnosed cancer are warranted, particularly in Hispanics and patients with solid tumors.